Influence of Weight Training on Straight Hit Capabilityat Wushu Club Unpatti Athletes - Ria Fauzi Tomagola; A. Fenanlampir; Jonas Solissa (Peneliti.net, 2023)
The aim of this research is to determine whether or not there is an effect of weight training on the straight punch ability of Unpatti wushu club athletes. This type of research is experimental research where the researcher wants to find out the effect of body weight training on the straight punch ability of Unpatti wushu club athletes with a one-group pre-test-post-test design. The results of the research show that the effect of weight training in the form of push-ups, Dips, and pull-ups has been proven to show real effectiveness, meaning that this training is effective in improving the straight punch ability of Unpatti wushu club athletes